Comparison of Spin-Echo T1- and T2-Weighted and Gradient-Echo T1-Weighted Images at 3T in Evaluating Very Preterm Neonates at Term-Equivalent Age - Sarikaya, B. (AJNR Am J Neuroradiol, 2013)
Term-equivalent imaging can assess myelination status in very preterm infants (<30 weeks' gestational age at birth). However, myelination assessment has yet to be compared among GRE-T1WI, SE-T1WI, and SE-T2WI at 3T. We aimed to compare the rates of myelination among those 3 sequences in 11 very preterm neonates who underwent 3T MR imaging at term-equivalent age and subsequently had normal neurologic development. On each sequence, 2 neuroradiologists individually assessed 22 structures. SE-T2WI depicted a higher myelination rate (present in 58.2%–66.4% of all structures) than either GRE-T1WI (51.6%–63.9%) or SE-T1WI (20.5%–38.5%), while GRE-T1WI had the highest interobserver agreement (κ, 0.56; P < .0001). Myelination was present in 90%–100% of patients within the corpus callosum splenium, DSCP, ICP, lateral lemniscus, and spinal tract/nucleus of cranial nerve V on SE-T2WI, and in the DSCP, ICP, lateral lemniscus, medial lemniscus, pyramidal decussation, PLIC, and superior cerebellar peduncle on GRE-T1WI, occurring in similar structures as previously shown at 1.5T and 1T. However, it is not clear whether these findings represent true myelination versus precursors to myelination.